Development of Student Management System - Tharindu Vidanagamage; D. Supiniduni Pragathika Piyadali; M.G. Shamali Dilrukshi; H.D. Shonali Romeshika; D.I De Silva; Dulanji Cooray (International Journal of Engineering and Management Research, 2022)
The focus of this essay is to demonstrate the consequences of using an automated web application for a student management system, how it eases the school operations, what technologies, tools, and methodologies used in developing the web application, a systematic explanation of the flow of functions through a proposed system and reveal the essential findings and expected results of the research. A student management system is a process or system that provides the data required to efficiently administer an educational institute. It supports the institution's strategic goals and provides an independent framework for collecting and storing data. By using management systems, administrative operations and formal procedures at educational institutions can be made much easier. Using student management systems, it is possible to maintain school records and data efficiently. The purpose of this research paper is to analyze the development of a web-based school management system that can be used by educational institutions to enhance the effectiveness and efficiency of learning, teaching, and administrative activities. This essay discusses the design and workflow of a developed web-based system and aims to present a complete overview of our well-authorized and authenticated school management system that was developed using Node JS, React JS, and MongoDB.